2012
DOI: 10.1134/s1070328412060085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of cadmium(II) complexes of tetramethylthiourea (Tmtu); X-ray structure of [Cd(Tmtu)2Cl2]

Abstract: The spectral characterization of cadmium(II) complexes of the general formula [Cd(Tmtu) 2 X 2 ] (Tmtu = tetramethylthiourea, X = Cl -, Br -, I -, and SCN -) as well as the X ray structure of one of them, [Cd(Tmtu) 2 Cl 2 ] (I) is described. In (I), the cadmium atom lies on a twofold rotation axis and has a distorted tetrahedral coordination environment defined by two S atoms of telramelhylthioures (Tmtu) ligands and two chloride ions. The crystal structure is stabilized by non classical intramolecular C-H⋅⋅⋅N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…In 13 C NMR, the >C=S, C-N and C-C resonances of Diaz in the complex are observed at 173.25 ppm, 40.20 ppm, and 19.11 ppm respectively (175.62 ppm, 39.76 ppm, 19.19 ppm for free Diaz). The upfield shift of 2.4 ppm in the >C=S resonance is in accordance with the data observed for other cadmium(II) complexes[1,3,4,10].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In 13 C NMR, the >C=S, C-N and C-C resonances of Diaz in the complex are observed at 173.25 ppm, 40.20 ppm, and 19.11 ppm respectively (175.62 ppm, 39.76 ppm, 19.19 ppm for free Diaz). The upfield shift of 2.4 ppm in the >C=S resonance is in accordance with the data observed for other cadmium(II) complexes[1,3,4,10].…”
supporting
confidence: 90%
“…These structural reports describe that in most of the cases, cadmium(II) complexes exist as neutral monomeric [3][4][5][6][7][8][9][10][11][12][13][14][15][16] or polymeric [17][18][19] molecules of the general formula [CdL 2 X 2 ] with the cadmium atom possessing a tetrahedral or distorted octahedral coordination environment respectively. In some cases, ionic complexes of the type [CdL 4 ]X 2 (X = nitrate or sulfonate) are also formed [21, 22].…”
mentioning
confidence: 99%
“…Optimization of the prediction of the structure of complex compounds and the results of previous studies using the Spartan'14 programs produced free energy data as shown in Table 6. Distorted tetrahedral -527.1549 Note: (*): synthesized complex (**): previously complex reported (Ahmad, et al, 2012) (a) (b) The structure prediction of [Cd(detu)2Br2] with a distorted tetrahedral geometry is in accordance with the experimental facts, has the lowest free energy and approaches the free energy of complex compounds that have been reported (Ahmad, et al, 2012). Based on the free energy data, the complex compound [Cd(detu)2Br2] with a distorted tetrahedral structure is the acceptable structure because it has the lowest free energy, which is -527.5574 kJ/mol.…”
Section: Structure Prediction Of Complex Compoundsupporting
confidence: 75%